An uncommon case of neurosarcoidosis presenting as trigeminal neuralgia - Lydia Slater; Andrew Slater; John Braca; Brian Le; Ryan Zimmerman (Greater Baltimore Medical Center, 2021)
Sarcoidosis is a systemic inflammatory condition causing increased immune system activity and manifesting as noncaseating granulomatous disease with the ability to affect multiple organ systems. Neurosarcoidosis is an uncommon presentation, with just 5-10% of patients with sarcoidosis experiencing intracranial disease. The diagnosis of neurosarcoidosis can be difficult, especially given the overlap of imaging findings with more common intracranial lesions. This case presents trigeminal neuralgia as the initial symptom of neurosarcoidosis and emphasizes the importance of a high clinical index of suspicion for neurosarcoidosis in patients with otherwise unexplained neurological symptoms.